Women with guide dog at a march - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two woman at a nighttime candlelight march. The woman on the right is holding the leash of a guide dog in her left hand and the arm of the woman on the left with her right hand. The woman on the left is wearing a hat, holding a lit candle, and is watching the dog. The dog appears to be a yellow labrador retriever and there are other people in the background.